PENYULUHAN PENCEGAHAN CYBER CRIME BAGI PENGGUNA MEDIA SOSIAL DI DESA SUKAJADI KECAMATAN CARITA - Wahyiah, Ita Rosita; Rahayu, Luis Fiska; Arasid, Mohammad Ikrom; Handayani, Putri; Rendiyani, M.; Nur Waris, Achmad; Marhamah, Aliatun; Nisa, Aulia; Sefriyandi, Andi; Pratama, Ahmad Yudha Eka (UNIVERSITAS SERAMBI MEKKAH, 2024)
The cyber crime prevention counseling for social media users in Sukajadi Village, Carita Subdistrict, aims to increase community awareness and knowledge about the threat of cyber crime and ways to protect themselves when using social media. Given the increasing use of social media among the village community, especially among teenagers and youth, the risk of being exposed to cyber crime attacks such as online fraud, account hacking, and spreading false information is higher. This extension program was implemented through a series of activities such as seminars, group discussions, and case simulations involving various layers of society, including youth, parents, and village officials. The results showed a significant increase in the community's understanding of the types of cybercrime and preventive measures that can be taken to avoid them. More than 80% of participants were able to identify signs of online fraud and take preventive measures such as setting account privacy and using strong passwords. In addition, the counseling also succeeded in building collective awareness on the importance of maintaining ethics in interacting on social media and reporting suspicious actions to the authorities.